Pengaruh Kualitas Sistem Informasi Manajemen Dan Struktur Organisasi Terhadap Efektivitas Pengambilan Keputusan Pada PT UT Quality Indonesia - tukino tukino (Computer Based Information System Journal, 2014)
This study aimed to examine the effect of Utilization Management Information Systems and Organizational Structure on Decision Effectiveness. Effectiveness Decision may be interpreted as a result of the company or individual in carrying out its work effectively, efficiently and legally controlled undertaken in order to achieve the mission and vision of the company. Factors that may affect the effectiveness of decision making allegedly dominant enough to have an influence on the effectiveness of decision making in Indonesia is PT UT Quality Utilization Management Information Systems and Organizational Structure. These factors are interrelated to one another on the Effectiveness of Decision Making in PT UT Quality Indonesia. Thus these factors have a relationship that can be combined to achieve higher effectiveness of decision making. Decision effectiveness is influenced by many other factors that need to add to the existing theories.